Primary End Point (Six Months) Results of the Ranibizumab for Edema of the mAcula in diabetes (READ-2) study - Nguyen, Quan Dong; Shah, Syed Mahmood; Heier, Jeffery S; Do, Diana V; Lim, Jennifer; Boyer, David; Abraham, Prema; Campochiaro, Peter A (Ophthalmology (Rochester, Minn.), 2009)
To compare ranibizumab with focal/grid laser or a combination of both in diabetic macular edema (DME). Prospective, randomized, interventional, multicenter clinical trial. A total of 126 patients with DME. Subjects were randomized 1:1:1 to receive 0.5 mg of ranibizumab at baseline and months 1, 3, and 5 (group 1, 42 patients), focal/grid laser photocoagulation at baseline and month 3 if needed (group 2, 42 patients), or a combination of 0.5 mg of ranibizumab and focal/grid laser at baseline and month 3 (group 3, 42 patients). The primary end point was the change from baseline in best-corrected visual acuity (BCVA) at month 6. At month 6, the mean gain in BCVA was significantly greater in group 1 (+7.24 letters, P = 0.01, analysis of variance) compared with group 2 (-0.43 letters), and group 3 (+3.80 letters) was not statistically different from groups 1 or 2. For patients with data available at 6 months, improvement of 3 lines or more occurred in 8 of 37 (22%) in group 1 compared with 0 of 38 (0%) in group 2 (P = 0.002, Fisher exact test) and 3 of 40 (8%) in group 3. Excess foveal thickness was reduced by 50%, 33%, and 45% in groups 1, 2, and 3, respectively. During a span of 6 months, ranibizumab injections by the current protocol had a significantly better visual outcome than focal/grid laser treatment in patients with DME.